Signalling by inositides : a practical approach - Shears, Stephen (Oxford ; New York : IRL Press at Oxford University Press, 1997)
"Inositide research has infiltrated numerous branches of biochemistry, physiology, and molecular biology. Consequently, methodological information has been scattered far and wide. This book unites a wide selection of the most fundamental and commonly used techniques. Contributors come from international signal transduction laboratories that have been actively involved in developing and refining these techniques. A unique feature of the book is a catalog of non-commercial sources of synthetic inositide analogues. Because there's an emphasis on broader applications instead of the more esoteric methods, this latest volume in the Practical Approach series is useful as an introduction and a refresher for new and seasoned inositologists, respectively."--Publisher
8. Mass assay of inositol 1,4,5-triphosphate and phospatidylinositol 4,5-bisphospate-- 9. Desalting inositol polyphospates by dialysis-- 10. The Ins(1,4,5)P₃ receptor-- 11. Purification and assay of inositol hexakisphosphate kinase and diphosphoinositol pentakisphosphate kinase-- 12. Phosphoinositide 3-kinase-- A1. List of suppliers-- A2. List of suppliers of inositol derivatives.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Inositol phosphates; Inositol; Phospholipids; Phospholipases; Cellular signal transduction; Inosite; Signal Transduction; Inositol Phosphates; Inositol; Phospholipids; Phospholipases; Inositol phosphates; Inositol; Phospholipides; Phospholipases; Transduction du signal cellulaire; SCIENCE -- Life Sciences -- Biochemistry; Inosite; Cellular signal transduction; Inositol; Inositol phosphates; Phospholipases; Phospholipids; Inositol; Signalen